2016
DOI: 10.1111/jce.13037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Improved Left Ventricular Systolic Function on the Recurrence of Ventricular Arrhythmia in Heart Failure Patients With an Implantable Cardioverter‐Defibrillator

Abstract: Overall survival was better and the recurrence of ventricular arrhythmia was lower in the patients with improved LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Twenty-four eligible observational studies were included in the meta-analysis. 5,[8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] No eligible randomized trials were identified. The search process and outputs are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-four eligible observational studies were included in the meta-analysis. 5,[8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] No eligible randomized trials were identified. The search process and outputs are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In 17 studies 5,913,1619,21-23,26-27,29,31 reporting data on all-cause mortality, there were more deaths among HFpREF patients (1311/7497, 17.5%) than among HFIEF patients (134/2281, 5.8%). This corresponded to a significantly lower risk of mortality in HFIEF patients, compared with HFpREF patients, with an estimated RR of 0.34 (CI 0.28–0.41, p < 0.001) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations